Exploring the Impact of Biological Agents on Protecting Against Experimental Periodontitis: A Systematic Review of Animal-Based Studies - Oliveira, Gabriela Ezequiel [UNESP]; da Silva Barbirato, Davi; de Menezes, Bruna Silva; Fuly, Milenna Silva; Pelegrine, Henrique Cassebe Ledo [UNESP]; Bonilha, Debora Caliendo [UNESP]; de Alencar, Julia Gabrielle Pereira [UNESP]; Theodoro, Leticia Helena [UNESP]; de Molon, Rafael Scaf [UNESP] (Wiley, 2024)
Aim: This systematic review was aimed at addressing the focused question: What is the protective potential of biological agents against alveolar bone resorption during the progression of experimental periodontitis (EP)? Material and Methods: The study protocol was registered in the Open Science Framework database (doi:10.17605/OSF.IO/3P2HY). A comprehensive literature search was conducted across PubMed, Web of Science, Cochrane Library, Scopus, and Embase databases up to December 2023. Inclusion criteria consisted of preclinical studies in animal models of EP that examined the effects of biological agents on preventing periodontal bone loss and reducing tissue inflammation. Studies were excluded if they (i) used non-EP animal models; (ii) focused on antimicrobial agents; (iii) centered on prebiotics or probiotics; (iv) evaluated compounds not classified as biologicals; or (v) included randomized clinical trials, clinical studies, or reviews. Eligibility was determined based on the PI/ECOs framework, and study quality was assessed using the SYRCLE risk-of-bias tool. Results: After screening an initial pool of 5236 records from databases, registries, and hand searches, 39 studies met the inclusion criteria. A total of 23 biological agents were evaluated across these studies. The majority of studies employed the ligature-induced model of EP to test the effectiveness of biologicals as preventive or therapeutic interventions. The dosage of biological agents and the duration of disease induction varied depending on the EP model. In all studies, the main outcome-alveolar bone loss, a hallmark of EP-was significantly inhibited by biological agents, which also reduced proinflammatory mediators when compared to untreated controls. A key strength of this review is the high number of studies included, most of which were classified as having low risk of bias. However, a notable limitation is the absence of a meta-analysis, the short follow-up periods in the included studies, and the heterogeneity among the compound dosages and route of administration. Conclusion: This systematic review demonstrates that biological agents are effective in reducing bone loss and mitigating inflammation during EP progression. Randomized clinical trials are needed to confirm these findings in human populations.
Keywords: alveolar bone; animal model; bone resorption; periodontal disease; periodontitis